2019
DOI: 10.4314/njb.v35i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of isolated compound of <i>Anadelphia afzeliana</i> (Rendle) Stapf on selected wood fungi and bacteria in Makurdi, Nigeria

Abstract: Anadelphia afzeliana was assessed for antimicrobial activity as an alternative to synthetic chemicals. A. afzeliana was collected from Orkar village, Gboko, Benue State. The specimen was pulverized. Methanol, ethyl acetate, and n-hexane solvents were used for extraction. Each solvent measured 1800 ml was added to 300 g of A. afzeliana. The mixture was left to soak for 48 hours. Extract was filtered and allowed to dry by evaporation. Dried extract was mixed with silica gel to run column chromatography. Compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The filtrates were evaporated to obtain dried extracts (Plate 1). Column Chromatography and Nuclear Magnetic Resonance (NMR) spectroscopic analysis Dried crude mixture of n-hexane and ethyl acetate extracts was run over silica gel with solvent mixtures of successive increasing polarity of hexane and ethyl acetate in the ratio of 95:5 -0:100, respectively, in column to produce pure compounds or fractions according to Ekhuemelo et al (2018). The fractions of the pure compounds were collected in well-labelled vials and allowed to dry (Plate 2).…”
Section: Plant Parts Collection and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The filtrates were evaporated to obtain dried extracts (Plate 1). Column Chromatography and Nuclear Magnetic Resonance (NMR) spectroscopic analysis Dried crude mixture of n-hexane and ethyl acetate extracts was run over silica gel with solvent mixtures of successive increasing polarity of hexane and ethyl acetate in the ratio of 95:5 -0:100, respectively, in column to produce pure compounds or fractions according to Ekhuemelo et al (2018). The fractions of the pure compounds were collected in well-labelled vials and allowed to dry (Plate 2).…”
Section: Plant Parts Collection and Preparationmentioning
confidence: 99%
“…Concentrations of 200 μg/mL and 100 μg/mL were prepared from each fraction and antibiotics respectively. The antibiotics used as control were Ketoconazole, fluconazole and Fulcin for fungi; and ciprofloxacin, sparfloxacin and cefuroxime for bacteria according to Ekhuemelo et al (2018).…”
Section: Determination Of Antimicrobial Activity Of Vitellaria Paradoxa Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gebashe et al (2020) reported soluble flavonoids, proanthocyanidins, iridoids, phenolic content, and phenolic acids phytochemicals from the profiles of thirteen medicinal grasses used for traditional medicine in South African. Ekhuemelo et al, (2018b) characterized stigmasterol from A. afzeliana. The potential effect of A. afzeliana to prevent or control the rate of termite activity could be the presence of resins in both methanol and aqueous extracts.…”
Section: Incidence Of Termite Attack On G Arborea T Ivorensis and D Oliveri Test Wood Samplesmentioning
confidence: 99%